Antonio Bergosa y Jordán (1748-1819), obispo de México: ¿ilustrado? ¿reaccionario? ¿contemporizador y oportunista? - Hamnett, Brian R. (El Colegio de México, A.C., 2009)
Inquisitor and prelate Antonio Bergosa y Jordán was one of the most important characters of the last two decades of the Spanish Colonial regime. However, little is known about him, and his role as Bishop of Oaxaca and elected Archbishop of Mexico, between 1800 and 1817, is not easily interpreted. Although he was close to many leaders of the Enlightenment, he was never among the most distinguished supporters of this movement. From 1810 on, he strongly  opposed  Mexican independence while defending the 1812 Constitution of Cadiz  as warrant  of the Spanish Monar- chy's unity.  This former  inquisitor welcomed,  nevertheless,  the abolition of the inquisition by the Cortes in 1813. Victim of Ferdinand's reaction starting  May 1814, Bergosa had to defend his conduct and reaffirm his loyalty.